👤

ex 23
simplificati raportul
[tex]a) \frac{15}{ \sqrt{3}* \sqrt{5} } [/tex]
 b)[tex] \frac{5- \sqrt{5} }{2 \sqrt{5} } [/tex]
c)[tex] \frac{3- \sqrt{3} } { 3\sqrt{2-} \sqrt6} } [/tex]
d)[tex] \frac{ 3\sqrt{8} +2 \sqrt{12}+ \sqrt{20} }{3 \sqrt{18}+ 2\sqrt{27} + \sqrt{48} } [/tex]

ex 24)scoateti factoorul sub radical 
a[tex] \sqrt{32a ^{3} b ^{10} } [/tex]) unde    a>0,b≤0:
b)[tex] \sqrt{27(a-b) ^{5} } ,[/tex] unde  a>b
c)[tex] \sqrt{-8(a-3) ^{3} } [/tex], unde a <3
d)[tex] \sqrt{(x-2) ^{3}(5-x) ^{5} },[/tex] unde 2<x<5
 
ex25)ntroduceti facotrul sub radical 
a)[tex]a \sqrt{3} , daca a <0[/tex]
b)[tex]x \sqrt{x} [/tex]
c)[tex]y \sqrt{-y} [/tex]
d)[tex](a-b) \sqrt{a-b} [/tex]
e)[tex](x-y) \sqrt{y-x} [/tex];



Răspuns :

15√15/15=√15
b) (5√5-5)/10=(√5-1)/2
c) (3-√3)(3√2+√6)/(18-6)=(9√2-3√6+3√6-3√2)/12=6√2/12=√2/2
d) (6√2+4√3+2√5)/(9√2+6√3+4√3)=2(3√2+2√3+√5)/(13√2+6√3)=
2(3√2+2√3+√5)(13√2-6√3)/(338-108)=2(78+26√6+13√10-18√6-36-6√15)/230=
(8√6+13√10-6√15+42)/115

a) 4ab^5√2a
b) 3(a-b)²√3(a-b)
c)  2(a-2)√-2(a-3)
d) (x-2)(5-x)²√(x-2)(5-x)

a)√3a²
b) √x³
c) √y³
d) √(a-b)³
e) √-(x-y)³